Geese, Elves, and the Duplicitous, "Diabolical" Landscaped Space of Reactionary Modernism: The Case of Holgersson, Hägerstrand, and Lorenz. Issue 1 (2nd January 2017) - Olwig, Kenneth R.
Abstract : Reactionary modernism is identified with Nazism, but modernism itself often has a reactionary dimension, which arguably can be traced partially back to the Renaissance construction of the modern map and, from it, perspectival, scenic landscape. The perspectival space of scenic landscape characteristically creates a dialectical hybrid consisting of, on the one hand, an invisible, lawful, geometric spatial framework expressing a modern scientific rationality, and on the other hand, a visible and holistic, but illusory visual scene of organic nature, place, and community appealing to reactionary affect, nostalgia, and emotion. This "duplicitous" dialectic can be termed "diabolic" as opposed to "symbolic." The construction and consequences of this hybrid are illustrated by how Selma Lagerlöf's Swedish geography reader cum children's story, The Wonderful Adventures of Nils Holgersson, affected the modernism of Torsten Hägerstrand's time-geographical spatial science and the reactionary modernism of Konrad Lorenz's Nazi biology, and by extension contemporary rewilding.